(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-1-81-93 The article presents an analysis of scientific literature devoted to the study of the linguistic local history direction of language learning. The aim of the work is to describe the origins of Russian linguistic local history, regional onomastics based on the use of textological analysis, descriptive method, elements of comparative and comparative-historical methods. The material of the research is presented by works that have a linguistic local history character, starting from the 30s of 18th century. Based on the analysis of scientific works of the 18th and early 19th centuries, including the linguistic local history component, the author comes to the following conclusions. Since the first third of the 18th century in Russia, there have been some fragmentary attempts at linguistic local lore commenting when describing settlements by historians, geographers, physicians, and biologists who participated in research expeditions across Russia. Of particular importance in this respect was the historical and regional studies activities of V.N. Tatishchev, who compiled detailed questions for the study of settlements in Russia, prepared the first part of the “Lexicon of Russian historical, geographical, political and civil”. The material of the research shows that the origins of scientific linguistic regional studies in Russia are associated with the activities of V.K. Trediakovsky and M.V. Lomonosov. M.V. Lomonosov consistently introduced the linguistic local history component into the research methodology, which was applied in practice in the compilation of the “Russian grammar”, in the organization of centralized work on the historical and geographical study of Russian settlements, in the development of the foundations of teaching Russian students in their native language. M.V. Lomonosov is the founder of the linguistic local history direction in Russian linguistics. The beginning of scientific regional onomastic research is associated with the activities of E.A. Bolkhovitinov, who for the first time in 1800 gave a detailed historical and linguistic description of the toponymy and microtoponymy of the Voronezh Territory. Key words: linguistic local history, regional onomastics, the origins of domestic linguistic local history, M.V. Lomonosov, E.A. Bolkhovitinov